The occurrence characteristics of ionospheric scintillation over Vietnam region during 2009-2012 period - Lan, Tran Thi; Minh, Le Huy; Fleury, R.; Phuong, Tran Viet; Thanh, Nguyen Ha (Vietnam Journal of Earth Sciences, 2016)
The statistic characteristics of ionospheric scintillation occurrence over Vietnam region have been studied using the continuous data from three GSV4004 receivers at Hanoi, Hue and Ho Chi Minh city during 2009-2012 period. The local time variation, seasonal variation and directional variation of scintillation occurrences in each stations were considered. The obtained results showed that the ionospheric scintillation over Vietnam region, mainly occurred at night time between 20 to 24 local time. The occurrence of ionospheric scintillation depend on the season and solar activity, with the maximum occurrence frequency on the equinox months (March, April and September, October) and significant enhancements on the strong active solar years (2011-2012). Over Vietnam region, ionospheric scintillation occurs concentratively on the equatorial ionisation anomaly crest, from the 13oN to 21oN geographic latitude with maximum at about 15oN. The ionospheric scintillation occurs mainly within the elevation angle smaller 40o and concentrate on some deterministic azimuth angles at each station. References Aarons J.,1982: Global morphology of ionospheric scintillations, Proc. IEEE, 70, 360-378. Abadi P., Saito S., and Srigutomo W., 2014: Low-latitude scintillation occurrences around the equatorial anomaly crest over Indonesia, Annales Geophys., 32, 7-17. Basu, S., S. Basu, J. Aarons, J.P. McClure, and M.D. Cousins, 1978: On the coexistence of kilometer- and meter-scale irregularities in the nighttime equatorial F region, Journal of Geophysical Research, 83 (A9), pp. 4219 - 4226. Basu S., E. Kudeki, S. Basu, C. E. Valladares and E. J. Weber, 1996: Scintillation, plasma drifts, and neutral winds in the equatorial ionosphere after sunset, Journal of Geophysical Research, Vol. 101, N.A12, 26795-26809. Beniguel Y., and Adam JP, 2007: Ionosphere Scintillation and their Effect on the Positioning Errors, IEEA, proccesding, France. Cervera M. A. and R. M. Thomas, 2006: Latitudinal and temporal variation of equatorial ionospheric irregularities determined from GPS scintillation observations, Ann.Geophys.,N.24, 3329-3341. Dierendonck V., A.J, John Klobuchar, Quyen Hua, 1993: Ionospheric Scintillation monitoring using commercial single frequency C/A code receivers, Proceedings of ION GPS-93. Kintner P. M., Ledvina B. M., and Paula E. R, 2007: GPS and ionospheric scintillations, Space weather, Vol.5, S09003, doi:10.1029/2007W000260. Trần Thị Lan, Lê Huy Minh, R. Fleury, P. Lassudrie Duchesne, A. Bourdillon, 2009: Bước đầu nghiên cứu nồng độ điện tử tổng cộng và nhấp nháy điện ly sử dụng số liệu các trạm thu GPS liên tuc ở Việt Nam, Tạp chí Các khoa học về Trái Đất. T. 31, 3, 212-223. Trần Thị Lan, Lê Huy Minh, 2011: Biến thiên theo thời gian của nồng độ điện tử tổng cộng và nhấp nháy điện ly theo số liệu GPS liên tuc ở Việt Nam, Tạp chí Các khoa học về Trái Đất. T. 33, N4, 681-689. Le Huy Minh, Amory-Mazaudier C.,Fleury R., Bourdillon A., Lassudrie-Duchesne P., L. Tran Thi, T. Nguyen Chien and T. Nguyen Ha, P. Vila, 2014 : Time variations of the total electron content in the Southeast Asian equatorial ionization anomaly for the period 2006-2011, Advances in Space Research, 54, 355-368. Rama Rao, P. V. S., Gopi Krishna, S., Niranjan, and Prasad, D. S. V. V. D, 2006: Study of spatial and temporal characteristics of L-band scintillation over the Indian low latitude region and their possible effects on GPS navigation, Ann. Geophys., 24, 1567-1580. Saito S., Maruyama T., Ishii M., Kubota M., Ma G., Chen Y., Li J., Duyen C. H., Truong T. L., 2008: Observation of small to large scale ionospheric irregularities associated with plasma bubbles with a transequatorial HF propagation experiment and spaced GPS receivers, Journal of Geophysical research, V.113, A12313. Valladares C. E., Villalobos J., Sheehan R., and Hagan M.P., 2004: Latitudinal extension of low laititude scintillations measured with a network of GPS receivers, Ann. Geophys., 22, 3155-3175. GSV GPS Silicon Valley, 2005: GSV4004/GSV4004A - GPS Ionospheric Scintillation & TEC Monitor, USER’S MANUAL.